Gambaran Pencapaian Target Tekanan Darah Sesuai JNC 8 Pada Pasien Pasca Stroke Yang Menjalani Terapi Antihipertensi Tunggal di RSU Bahteramas Provinsi Sulawesi Tenggara Tahun 2014 - Leorita, Mesi; Fiandari, Dwi Asti (Fakultas Farmasi Universitas Halu Oleo, 2015)
Hypertension is a main risk factor that causes stroke and also a most significant role to the multiple stroke occurrences. The post-stroke patients are recommended to use appropriate anti-hypertension to achieve blood pressure target. The aim of this research is to depict achievement of blood pressure target according to JNC 8 of the post-stroke patients in Bahteramas Hospital of Southeast Sulawesi Province during 2014. This is a non-experimental research which is carried out with cohort study retrospective method. Secondary data were obtained from medical records of post-stroke patients who acquired single oral anti-hypertension therapy. Univariate statistical analysis was conducted to understand general profile of the post-stroke patients with hypertension, and inspect target achievement of blood pressure therapy according to JNC 8 at any anti-hypertension therapies. There are 55 data of anti-hypertension use from 45 post-stroke patients. Four types of anti-hypertension therapy used by the research subjects including amlodipine 1 x 10 mg, furosemide 1 x 40 mg, captopril 3 x 50 mg, and candesartan 1 x 8 mg. The entire result of research for age group of < 60 years old shows only 20.51% research subjects achieved the blood pressure target of < 140/90 mmHg. For the patients more than 60 years old, the result showed 56.25% research subjects achieved the therapy targeted. Therapy by using amlodipine provides a higher number of research subjects achieving blood pressure target according to JNC 8, both for age group of < 60 years old and > 60 years old. The small achievement percentage of the therapy target is perhaps caused by non-optimal use of the anti-hypertension.Keywords: Post-stroke, anti-hypertension, blood pressure therapy target of JNC 8